ASPECTS REGARDING THE CONNECTION OF THE PIPELINES WITH PERPENDICULAR AXES - Mârza Carmen; Iacob Georgiana; Duca Eugenia (Journal of Industrial Design and Engineering Graphics, 2009)
The special dynamics defining the field of installations both from the point of view of technologies and new materials used to implement them, requires a permanent research concerning the components of tubing. This paper concerns the way branch type connections between circular section pipelines can be solved so that durable and waterproof joining is produced, with reasonable load loss and minimum turbulence in flow.